Electronic Word of Mouth (eWOM) on restaurants in Sarawak - Tan, Chin Choo; Jamil B.,; Aryty A.,; Adrian Daud, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Competitiveness in food service industry and the introduction of social media have created a challenge in restaurant industry. This is because restaurant operators need to adapt to the new trend of electronic communication technology which may give great impact to their companies. The purpose of this study is to identify the determinant factors of customer satisfaction which may direct or indirectly affect customer return intention and involvement of electronic word of mouth (eWOM) through social media. A review of the literature mentioning the type of restaurant experiences chosen and the development of eWOM was studied. Regression analysis was adopted to investigate the hypothesis formed. Identification and implementation of these technologies can help in building a sustainable competitive advantage for restaurants. The findings of this study revealed that restaurant experiences had a high positive relationship with customer satisfaction. Atmosphere and customer satisfaction also indicated the respective contributions made to eWOM.